Wind-Induced Coupling Vibration Effects of High-Voltage Transmission Tower-Line Systems - Meng Zhang; Guifeng Zhao; Lulu Wang; Jie Li (Shock and Vibration)
A three-dimensional finite element model of a 500 kV high-voltage transmission tower-line coupling system is built using ANSYS software and verified with field-measured data. The dynamic responses of the tower-line system under different wind speeds and directions are analyzed and compared with the design code. The results indicate that wind speed plays an important role in the tower-line coupling effect. Under the low wind speed, the coupling effect is less obvious and can be neglected. With increased wind speed, the coupling effect on the responses of the tower gradually becomes prominent, possibly resulting in the risk of premature failure of the tower-line system. The designs based on the quasi-static method stipulated in the current design code are unsafe because of the ignorance of the adverse impacts of coupling vibration on the transmission towers. In practical engineering, when the quasi-static method is still used in design, the results for the design wind speed should be multiplied by the corresponding tower-line coupling effect amplifying coefficient δ.